Safety assessment of tolvaptan: real-world adverse event analysis using the FAERS database - Cao, Peiyang; Wang, Qian; Wang, Yan; Qiao, Qing; Yan, Liyuan (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to analyze the adverse drug events (ADEs) associated with tolvaptan in the Food and Drug Administration Adverse Event Reporting System database from the fourth quarter of 2009 to the second quarter of 2024.MethodsAfter standardizing the data, various signal detection techniques, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network, and Multi-Item Gamma Poisson Shrinker, were employed for analysis.ResultsAmong the 7,486 ADE reports where tolvaptan was the primary suspected drug, a total of 196 preferred terms were identified, spanning 24 different system organ classes. Specifically, hepatobiliary disorders, renal and urinary disorders, and metabolic and nutritional disorders were found to be characteristic adverse reactions associated with tolvaptan. Additionally, uncommon but notable ADE signals were observed, such as renal cyst rupture, renal cyst infection, polycystic liver disease, and renal cyst hemorrhage. These several ADEs have not been referred to in the previous literature. Notably, strong ADE signals were detected for decreased urine osmolality [n = 5, ROR 149.74, PRR 149.7, IC (Information Component) 7.13, EBGM (Empirical Bayes Geometric Mean) 139.79], osmotic demyelination syndrome (n = 38, ROR 128.47, PRR 128.25, IC 6.92, EBGM 120.91), and pulmonary-related tumors such as bronchial metastatic carcinoma, bronchial carcinoma, metastatic small cell lung carcinoma, and small cell lung carcinoma. In the concomitant medication analysis of 7,486 suspected adverse drug reaction reports related to tolvaptan, the top three drugs most commonly used in combination with tolvaptan were furosemide, spironolactone, and amlodipine.ConclusionWhile tolvaptan provides therapeutic benefits, it poses a risk of significant adverse reactions. Clinicians should closely monitor the occurrence of events related to hepatobiliary disorders, renal and urinary disorders, metabolic and nutritional disorders, as well as benign, malignant, and indeterminate tumors during its clinical use.